2012
DOI: 10.3325/cmj.2012.53.48
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of tuberculosis at autopsies in a large hospital in Zagreb, Croatia: a 10-year retrospective study

Abstract: AimTo assess the frequency and forms of pulmonary tuberculosis at autopsy in a high-traffic hospital in the capital city of a country with a low tuberculosis incidence.MethodsWe performed a retrospective search of autopsy data from the period 2000 to 2009 at Sestre Milosrdnice University Hospital Center, Zagreb, Croatia. We also examined patients’ records and histological slides.ResultsOf 3479 autopsies, we identified 61 tuberculosis cases, corresponding to a frequency of 1.8%. Active tuberculosis was found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
(20 reference statements)
2
4
0
Order By: Relevance
“…Postmortem studies in the pre-HIV era and in settings with varying TB burden have shown that it was common for clinicians to underrecognize TB . In this study, patients with culture-negative PTB were less likely to have cough, weight loss, and pulmonary cavitation, consistent with prior, more limited studies .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Postmortem studies in the pre-HIV era and in settings with varying TB burden have shown that it was common for clinicians to underrecognize TB . In this study, patients with culture-negative PTB were less likely to have cough, weight loss, and pulmonary cavitation, consistent with prior, more limited studies .…”
Section: Discussionsupporting
confidence: 83%
“…Postmortem studies in the pre-HIV era and in settings with varying TB burden have shown that it was common for clinicians to underrecognize TB. [21][22][23][24] In this study, patients with culture-negative PTB were less likely to have cough, weight loss, and pulmonary cavitation, consistent with prior, more limited studies. 4,9 The list of differential diagnoses in these patients can be broad, ranging from other slowly progressing infectious diseases such as histoplasmosis to autoimmune diseases such as sarcoidosis, making its diagnosis even more challenging.…”
Section: Jama Network Open | Infectious Diseasessupporting
confidence: 85%
“…In a Croatian hospital, clinically undiagnosed active tuberculosis was diagnosed on autopsy in 33 subjects (54%), of which 70% were male. [18] In a meta-analysis, about one-third of death certificates were found to be erroneous and about half of the autopsies revealed findings that were not clinically suspected when the subjects were alive. [19] The proportion of deaths due to electrocution in KMD area was significantly higher than that in other areas (p = 0.00005; OR = 0.327).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of these cases were seen in the elderly; pulmonary tuberculosis accounted for 54% of these deaths, with miliary tuberculosis accounting for 35% (21). A Croatian study revealed active tuberculosis in 1.8% of cases, 76% of which were clinically unrecognized (22).…”
Section: Discussionmentioning
confidence: 99%